Menata Domain Psikologis Pasca Bencana - Muhammad Idrus (Universitas Islam Indonesia, 2005)
A member of International aid from Tiongkok Wu Min recently has finistied the task at disaster region of tsunami and returned to the mother land. The press has chance to interview Wu Min. Wu Min is still look tired, always feel tired body, can not sleep, decrease willing to eatso that his bodyweight is decrease drastically. Although Wu Min has come back to home, but still shadow in Wu Min's memory the situation of disaster at the field where tsunami happened, instead, it is difficult to lose from mind. Wu Min told that he undergoes many accidents in conducting aid activities to the victims at the field, and Wu Min sees by eyes the situation of disaster above-mentioned. Because of heart and feeling shockdown and work so hard at that region, Wu Min is look like rather depression (Radio of China broadcasting in Indonesia).